2020
DOI: 10.1111/tpj.15032
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis RING‐type E3 ubiquitin ligase XBAT35.2 promotes proteasome‐dependent degradation of ACD11 to attenuate abiotic stress tolerance

Abstract: Plants employ multiple mechanisms to cope with a constantly changing and challenging environment, including using the ubiquitin proteasome system (UPS) to alter their proteome to assist in initiating, modulating and terminating responses to stress. We previously reported that the ubiquitin ligase XBAT35.2 mediates the proteasome-dependent degradation of Accelerated Cell Death 11 (ACD11) to promote pathogen defense. Here, we demonstrate roles for XBAT35.2 and ACD11 in abiotic stress tolerance. As seen in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…XBAT35 is involved in plant thermomorphogenesis XBAT35 belongs to a small E3 ubiquitin ligase gene family that is involved in abiotic stress responses, apical hook curvature and lateral root development in Arabidopsis (Nodzon et al, 2004;Carvalho et al, 2012;Liu et al, 2017;Li et al, 2020;Yu et al, 2020). We obtained several gene-edited loss-of-function mutant alleles of XBAT35 (Figure S1), and checked their thermoresponsive hypocotyl phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…XBAT35 is involved in plant thermomorphogenesis XBAT35 belongs to a small E3 ubiquitin ligase gene family that is involved in abiotic stress responses, apical hook curvature and lateral root development in Arabidopsis (Nodzon et al, 2004;Carvalho et al, 2012;Liu et al, 2017;Li et al, 2020;Yu et al, 2020). We obtained several gene-edited loss-of-function mutant alleles of XBAT35 (Figure S1), and checked their thermoresponsive hypocotyl phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…5), likely promoting the deubiquitination and stabilization of VPS23A, which seems to contradict with the promoted degradation of VPS23A under ABA stimulation. Considering that VPS23A stability is modulated by the E3 ligase XBAT35.2, a previous study reported that ABA treatment also stabilizes XBAT35.2 (52). Hence, we surmised whether the increased amount of UBP12 and UBP13 could also deubiquitinate and thus stabilize XBAT35.2 to reduce the amount of VPS23A in response to ABA.…”
Section: Ubp12 and Ubp13 Interact With Vps23a To Regulate Aba Responsesmentioning
confidence: 93%
“…The skipping of the exon-8 has been characterized in Arabidopsis and shown to produce a nuclear localization signal (NLS)-lacking variant, XBAT35.2, consistently localized in the cytoplasm, in contrast with the nuclear localization of the full-length transcript XBAT35.1 [ 44 ]. The E3 ligase isoform XBAT35.2, functioning in the ubiquitin-proteasome system by targeting specific substrates, has been shown to regulate the morphogenesis of Arabidopsis plantlets [ 44 ] and is thought to play dual roles in biotic and abiotic stress responses [ 45 , 46 ]. Interestingly, when Arabidopsis young plants were treated with the phytohormone ABA, the transcription and translation of XBAT35.2 were induced, negatively controlling the tolerance to abiotic stress [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The E3 ligase isoform XBAT35.2, functioning in the ubiquitin-proteasome system by targeting specific substrates, has been shown to regulate the morphogenesis of Arabidopsis plantlets [ 44 ] and is thought to play dual roles in biotic and abiotic stress responses [ 45 , 46 ]. Interestingly, when Arabidopsis young plants were treated with the phytohormone ABA, the transcription and translation of XBAT35.2 were induced, negatively controlling the tolerance to abiotic stress [ 46 ]. Given the fact that ripening of the grape berry, a non-climacteric fruit, is highly dependent on ABA, the increasing predominance of XBAT35.2 from pré-véraison to mid-ripening could have a particular significance in this context.…”
Section: Discussionmentioning
confidence: 99%